Non-aqueous electrolyte power storage device and using method of non-aqueous electrolyte power storage device
By adding a specific concentration of lithium boric acid oxylate to the nonaqueous electrolyte energy storage element, the problem of easy short-circuitation and high resistance of metal lithium negative electrodes is solved, and a nonaqueous electrolyte energy storage element with low charge transfer resistance and high durability is achieved.
Patent Information
- Application Number
- JP2023121663
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-06
AI Technical Summary
In the non-aqueous electrolyte energy storage element, short circuit is prone to occur when metal lithium is used as the negative electrode active substance, and the charge and discharge performance of the non-aqueous electrolyte energy storage element using polymer as the main component is limited by a high charge transfer resistance.
In the nonaqueous electrolyte energy storage element, lithium salts containing oxylate composite anions, especially lithium boric acid oxylate, are introduced as additives for the nonaqueous electrolyte, and the concentration is controlled between 0.1% and 5%, and operated at an environment above 40°C.
It effectively reduces the charge transfer resistance, suppresses the occurrence of short circuits, increases the number of charge and discharge times, and enhances the durability of the components.
Smart Images

Figure 2025018174000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a nonaqueous electrolyte electricity storage element and a method for using the nonaqueous electrolyte electricity storage element. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. Non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring charge-transporting ions between the electrodes. As non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used.
[0003] In recent years, instead of non-aqueous electrolyte solutions in which an electrolyte salt is dissolved in a liquid such as an organic solvent, non-aqueous electrolytes using polymer materials such as polyethylene oxide and polycarbonate have been attracting attention (see Patent Document 1). In addition, non-aqueous electrolyte storage elements may use metallic lithium as a negative electrode active material with high energy density (see Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-185195 A [Patent Document 2] JP 2016-100065 A Summary of the Invention [Problem to be solved by the invention]
[0005] A non-aqueous electrolyte storage element having a negative electrode containing metallic lithium as a negative electrode active material has the disadvantage that a short circuit is likely to occur due to repeated charging and discharging. In addition, in a non-aqueous electrolyte storage element, it is desirable that the charge transfer resistance between the non-aqueous electrolyte and the electrode is low in terms of charge and discharge performance, etc. In particular, a non-aqueous electrolyte storage element using a non-aqueous electrolyte containing a polymer as a main component tends to have a higher charge transfer resistance than a non-aqueous electrolyte storage element using a non-aqueous electrolyte solution that is liquid at room temperature, and it is desirable to reduce the charge transfer resistance in a non-aqueous electrolyte storage element using a non-aqueous electrolyte containing a polymer as a main component.
[0006] An object of the present invention is to provide a nonaqueous electrolyte storage element that uses a nonaqueous electrolyte containing a polymer as a main component, which has low charge transfer resistance and is suppressed from causing a short circuit due to repeated charging and discharging, and a method for using such a nonaqueous electrolyte storage element. [Means for solving the problem]
[0007] A nonaqueous electrolyte storage element according to one aspect of the present invention comprises a negative electrode having metallic lithium at least in a charged state, and a nonaqueous electrolyte containing a polymer as a main component, wherein the nonaqueous electrolyte further contains a salt having an oxalato complex anion containing elemental boron, and the content of the salt in the nonaqueous electrolyte is 0.1% by mass or more and 5% by mass or less.
[0008] A method for using a nonaqueous electrolyte storage element according to another aspect of the present invention comprises operating the nonaqueous electrolyte storage element according to the aspect of the present invention in an environment at 40° C. or higher. Effect of the Invention
[0009] According to one aspect of the present invention, it is possible to provide a nonaqueous electrolyte storage element that uses a nonaqueous electrolyte containing a polymer as a main component, the nonaqueous electrolyte storage element having low charge transfer resistance and suppressing the occurrence of short circuits due to repeated charging and discharging, and a method for using such a nonaqueous electrolyte storage element. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a nonaqueous electrolyte electricity storage element. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] First, an outline of the nonaqueous electrolyte electricity storage element and the method of using the nonaqueous electrolyte electricity storage element disclosed in this specification will be described.
[0012] [1] A nonaqueous electrolyte storage element according to one aspect of the present invention comprises a negative electrode having metallic lithium at least in a charged state, and a nonaqueous electrolyte containing a polymer as a main component, wherein the nonaqueous electrolyte further contains a salt having an oxalato complex anion containing elemental boron, and the content of the salt in the nonaqueous electrolyte is 0.1% by mass or more and 5% by mass or less.
[0013] The nonaqueous electrolyte storage element described in [1] above is a nonaqueous electrolyte storage element using a nonaqueous electrolyte containing a polymer as a main component, and has low charge transfer resistance and suppresses the occurrence of short circuits due to repeated charging and discharging. The reason for this is unclear, but the following reason is presumed. Since the nonaqueous electrolyte contains a salt having an oxalato complex anion containing a boron element, a low-resistance and good coating (SEI) derived from such a salt is formed on the negative electrode surface. In the nonaqueous electrolyte storage element described in [1] above, it is presumed that the content of the salt having an oxalato complex anion containing a boron element is 0.1 mass% or more and 5 mass% or less, and such a coating is formed with an appropriate thickness, thereby reducing the charge transfer resistance. In addition, in a nonaqueous electrolyte storage element having a negative electrode containing metallic lithium as a negative electrode active material, metallic lithium may be precipitated in a dendritic form on the negative electrode surface during charging (hereinafter, metallic lithium in a dendritic form is referred to as "dendrite"). When the dendrites grow and penetrate the separator to come into contact with the positive electrode, they cause a short circuit. In contrast, in the nonaqueous electrolyte storage element described in [1] above, the low-resistance and good coating is formed with an appropriate thickness as described above, so that current concentration due to overvoltage during charging is suppressed, and dendrites are less likely to grow. Therefore, in the nonaqueous electrolyte storage element described in [1] above, it is presumed that the occurrence of short circuits due to repeated charging and discharging is suppressed, the number of charging and discharging cycles before a short circuit occurs is large, and multiple charging and discharging can be performed satisfactorily.
[0014] The negative electrode provided in the nonaqueous electrolyte storage element described in [1] above may have metallic lithium at least in a charged state, and may not have metallic lithium in a discharged state. For example, the nonaqueous electrolyte storage element may be configured such that metallic lithium is deposited on at least a part of the surface of the negative electrode during charging, so that the negative electrode has metallic lithium in a charged state, and the metallic lithium on the surface of the negative electrode is substantially completely dissolved into the nonaqueous electrolyte during discharging, so that the negative electrode does not substantially have metallic lithium in a discharged state. Here, the "charged state" refers to a state in which the nonaqueous electrolyte storage element is charged to a fully charged state by adopting a charge and discharge condition recommended or specified for the nonaqueous electrolyte storage element. For example, if a charger for the nonaqueous electrolyte storage element is prepared, the charger may be used to charge the nonaqueous electrolyte storage element.
[0015] The term "main component" refers to the component that is contained in the largest amount. That is, in the nonaqueous electrolyte of the nonaqueous electrolyte storage element described in [1] above, the polymer is the component that is contained in the largest amount.
[0016] The salts contained in the non-aqueous electrolyte are subjected to qualitative and quantitative analysis by ion chromatography (IC). The IC analysis equipment used is the "Dionex ICS-5000+" manufactured by Thermo Fisher Scientific. Water is used as the eluent. The specific procedure is as follows. A series of measurements is performed consecutively under the same conditions. First, the nonaqueous electrolyte storage element is disassembled to remove the nonaqueous electrolyte present outside the electrode body. After measuring the mass of the removed nonaqueous electrolyte, a certain amount of a suitable solvent (e.g., acetonitrile, etc.) is used to extract the salt, which is used as a measurement sample. When extracting the salt, the nonaqueous electrolyte may be completely dissolved using a certain amount of a suitable solvent (e.g., acetonitrile, etc.). (qualitative analysis) The measurement sample (salt) is subjected to IC analysis. The components contained in the measurement sample are predicted from the peak positions of each peak in the obtained ion chromatogram. A known sample of the predicted components (hereinafter referred to as "predicted components") is subjected to IC analysis. The retention time of the peak corresponding to the predicted component in the measurement sample is compared with the retention time of a known sample of the predicted component, and if they match, the prediction is presumed to be correct. (Quantitative analysis) Quantitative analysis is performed using the calibration curve method. First, IC measurements are performed on a known sample of a predicted component with a known content (mass), and a calibration curve is created by calculating the peak area. The calibration curve is calculated using the coefficient of determination (r 2 ) is 0.99 or more and 1 or less. The content obtained from the calibration curve and the area of the peak of the predicted component of the measurement sample is the content (mass) of the predicted component in the measurement sample. The above procedure is performed for all peaks detected in the IC analysis of the measurement sample, and the content obtained is the content (mass) of each predicted component. The content (mass) of salt having an oxalato complex anion containing boron element among the predicted components relative to the mass of the extracted non-aqueous electrolyte is the content of salt having an oxalato complex anion containing boron element in the non-aqueous electrolyte.
[0017] [2] In the nonaqueous electrolyte storage element according to the above [1], the salt may be lithium bis(oxalato)borate.
[0018] The nonaqueous electrolyte storage element described in [2] above has a lower charge transfer resistance and is more inhibited from causing a short circuit due to repeated charging and discharging.
[0019] [3] In the nonaqueous electrolyte storage element according to the above [1] or [2], the content of the salt in the nonaqueous electrolyte may be 0.5% by mass or more and 2% by mass or less.
[0020] The nonaqueous electrolyte storage element described in [3] above has a lower charge transfer resistance and is more inhibited from causing short circuits due to repeated charging and discharging.
[0021] [4] The nonaqueous electrolyte electricity storage element according to any one of [1] to [3] above may be operated in an environment of 40° C. or higher.
[0022] The nonaqueous electrolyte storage element described in [4] above is more effectively prevented from short-circuiting due to repeated charging and discharging. It is presumed that the reason for this effect is that operation at a relatively high temperature increases the ionic conductivity of the nonaqueous electrolyte and decreases the charge transfer resistance, thereby reducing overvoltage and more effectively suppressing the growth of dendrites due to current concentration.
[0023] [5] A method for using a nonaqueous electrolyte storage element according to another aspect of the present invention comprises operating the nonaqueous electrolyte storage element according to any one of [1] to [4] above in an environment of 40° C. or higher.
[0024] According to the method for using a nonaqueous electrolyte storage element described in [5] above, a nonaqueous electrolyte storage element using a nonaqueous electrolyte containing a polymer as a main component can be used in a state of low charge transfer resistance and with the occurrence of short circuits due to repeated charging and discharging suppressed. That is, according to the method for using a nonaqueous electrolyte storage element described in [5] above, the number of repeated charging and discharging cycles before a short circuit occurs is large, and multiple charging and discharging can be performed satisfactorily.
[0025] A nonaqueous electrolyte storage element according to one embodiment of the present invention, a method for using the nonaqueous electrolyte storage element, an electricity storage device, a method for manufacturing a nonaqueous electrolyte storage element, and other embodiments will be described in detail. Note that the names of the components (elementary components) used in each embodiment may differ from the names of the components (elementary components) used in the background art.
[0026] <Non-aqueous electrolyte electricity storage element> A nonaqueous electrolyte storage element (hereinafter, also simply referred to as "storage element") according to one embodiment of the present invention includes an electrode assembly having a positive electrode, a negative electrode, and a separator, a nonaqueous electrolyte, and a container that contains the electrode assembly and the nonaqueous electrolyte. The electrode assembly is usually of a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are laminated with a separator interposed therebetween, or of a wound type in which a positive electrode and a negative electrode are laminated with a separator interposed therebetween and wound. The nonaqueous electrolyte exists in a state in which it is impregnated in the positive electrode, the negative electrode, and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as "secondary battery") will be described.
[0027] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.
[0028] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 -2 The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).
[0029] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.
[0030] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.
[0031] The positive electrode active material layer contains a positive electrode active material and, as necessary, optional components such as a conductive agent, a binder, a thickener, and a filler.
[0032] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≦x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Co (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2(0≦x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β). Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Niγ Mn (2-γ) O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more may be mixed and used.
[0033] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. In addition, when a composite of the positive electrode active material and another material is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. The "average particle size" means a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).
[0034] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both dry and wet methods.
[0035] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.
[0036] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in combination. For example, a material in which carbon black and CNT are combined may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.
[0037] The content of the conductive agent in the positive electrode active material layer is preferably from 1 mass % to 10 mass %, more preferably from 3 mass % to 9 mass %. By setting the content of the conductive agent in the above range, the energy density of the nonaqueous electrolyte storage element can be increased.
[0038] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0039] The content of the binder in the positive electrode active material layer is preferably from 1% by mass to 10% by mass, and more preferably from 3% by mass to 9% by mass. By setting the content of the binder in the above range, the positive electrode active material can be stably maintained.
[0040] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, this functional group may be deactivated in advance by methylation or the like.
[0041] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, and mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.
[0042] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0043] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode.
[0044] The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, and nickel-plated steel, or alloys thereof, and carbonaceous materials are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils, vapor deposition films, meshes, and porous materials, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.
[0045] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.
[0046] The negative electrode active material layer has metallic lithium at least in a charged state. That is, the negative electrode active material layer is a layer containing metallic lithium at least in a charged state. Metallic lithium is a component that functions as a negative electrode active material. Metallic lithium may exist as pure metallic lithium consisting essentially of lithium element only, or may exist as a lithium alloy containing other elements. Examples of lithium alloys include lithium silver alloys, lithium zinc alloys, lithium calcium alloys, lithium aluminum alloys, lithium magnesium alloys, and lithium indium alloys. The lithium alloy may contain multiple elements other than lithium.
[0047] The negative electrode active material layer may be a layer substantially composed of metallic lithium. The content of metallic lithium in the negative electrode active material layer may be 90% by mass or more, 99% by mass or more, or 100% by mass.
[0048] The negative electrode active material layer may be a pure metallic lithium foil or a lithium alloy foil. The negative electrode active material layer may be a non-porous layer (solid layer). The negative electrode active material layer may also be a porous layer having particles containing metallic lithium. The negative electrode active material layer, which is a porous layer having particles containing metallic lithium, may further have, for example, resin particles, inorganic particles, etc.
[0049] The negative electrode active material layer, i.e., the layer containing metallic lithium, is preferably a layer that exists even in a discharged state, i.e., a layer that exists in all states from a charged state to a discharged state. The average thickness of the negative electrode active material layer in a discharged state is preferably 5 μm or more and 1,000 μm or less, more preferably 10 μm or more and 500 μm or less, and even more preferably 30 μm or more and 300 μm or less. The average thickness of the negative electrode active material layer is the average of thicknesses measured at any five points. When the negative electrode active material containing metallic lithium exists even in a discharged state, and preferably the average thickness is equal to or more than the above lower limit, a sufficient amount of metallic lithium is present, so that the capacity retention rate after charge-discharge cycles of the nonaqueous electrolyte storage element is increased.
[0050] In addition, in the case of a nonaqueous electrolyte storage element configured such that metallic lithium is precipitated on at least a portion of the surface region of the negative electrode during charging and substantially all of the metallic lithium of the negative electrode is dissolved into the nonaqueous electrolyte as lithium ions during discharging, the negative electrode may not substantially have a negative electrode active material layer in a discharged state.
[0051] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.
[0052] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the energy storage element.
[0053] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.
[0054] (Non-aqueous electrolyte) The non-aqueous electrolyte contains a polymer as a main component. The non-aqueous electrolyte further contains a salt having an oxalato complex anion containing a boron element (hereinafter also referred to as "salt X"). The non-aqueous electrolyte usually further contains a lithium salt other than salt X as a supporting salt. Salt X may function as a supporting salt.
[0055] As the polymer, for example, a known polymer used in a conventional polymer solid electrolyte can be used. The polymer preferably has a structural unit including a structure having a property of coordinating with lithium ions. By coordinating lithium ions to the polymer, the non-aqueous electrolyte can exhibit good ion conductivity even in a solid state. The content of the structural unit including a structure having a property of coordinating with lithium ions relative to the total structural units of the polymer is preferably 50 mol% or more and 100 mol% or less, more preferably 70 mol% or more and 100 mol% or less, even more preferably 90 mol% or more and 100 mol% or less, and even more preferably 97 mol% or more and 100 mol% or less.
[0056] The structural unit having the property of coordinating with lithium ions is preferably a structural unit having a structure having a polar group, more preferably a structural unit having a structure having a polar group containing at least one of an oxygen atom and a nitrogen atom, and even more preferably a structural unit having a structure having a polar group containing an oxygen atom. Examples of the polar group containing an oxygen atom include a carbonate group (-OCOO-), an ether group (-O-), a carbonyl group (-CO-), and an ester group (-COO-). Among these, a carbonate group or an ether group is preferred, and a carbonate group is more preferred.
[0057] The structural unit containing a structure having a carbonate group may be a structural unit containing a structure derived from an unsaturated cyclic carbonate. The unsaturated cyclic carbonate is a cyclic carbonate containing a carbon-carbon unsaturated bond in the ring structure. The structural unit may be a structural unit containing a structure having a cyclic carbonate structure in which a part of the ring structure constitutes a part of the main chain.
[0058] Examples of the unsaturated cyclic carbonate include vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, vinyl vinylene carbonate, and allyl vinylene carbonate, with vinylene carbonate being preferred.
[0059] Examples of structural units containing a structure having a carbonate group include -[CH2-CHR 1 -OCOO]-(R 1 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms.) and other structural units having a structure having a carbonate group in the main chain and no ring structure are also included.
[0060] Examples of structural units containing a structure having an ether group include structural units derived from alkylene oxides such as ethylene oxide and propylene oxide. Such structural units are usually represented by the formula -[CHR 2 -CHR 3 -O]-(R 2 and R 3 are each independently a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms. The structural unit has a structure represented by the following formula: The structural unit is a structural unit containing a structure having an ether group in the main chain.
[0061] The structural unit including a structure having the property of coordinating to a lithium ion may be a structural unit including a structure having a cyclic ether structure, a cyclic ester structure, or a cyclic carbonate structure in a side chain.
[0062] The cyclic ether structure refers to a ring structure containing an ether group. Examples of the cyclic ether structure include an oxetane structure, a tetrahydrofuran structure, and a tetrahydropyran structure.
[0063] The cyclic ester structure refers to a ring structure containing an ester group. The cyclic ester structure is a so-called lactone structure. Examples of the cyclic ester structure include a β-propiolactone structure, a γ-butyrolactone structure, a δ-valerolactone structure, and an ε-caprolactone structure.
[0064] The cyclic carbonate structure refers to a ring structure containing a carbonate group. Examples of the cyclic carbonate structure include an ethylene carbonate structure and a 1,3-propylene carbonate structure (a trimethylene carbonate structure).
[0065] Examples of monomers that give structural units containing a structure having a cyclic ether structure, a cyclic ester structure, or a cyclic carbonate structure in the side chain include monomers having a carbon-carbon unsaturated double bond and a cyclic ether structure, such as tetrahydrofurfuryl (meth)acrylate and 2-tetrahydropyranyl (meth)acrylate, monomers having a carbon-carbon unsaturated double bond and a cyclic ester structure, such as β-propiolactyl (meth)acrylate and γ-butyrolactyl (meth)acrylate, and monomers having a carbon-carbon unsaturated double bond and a cyclic carbonate structure, such as glycerin carbonate (meth)acrylate, vinyl ethylene carbonate, and allyl ethylene carbonate. The monomer that gives structural units containing a structure having a cyclic ether structure, a cyclic ester structure, or a cyclic carbonate structure in the side chain is preferably a (meth)acrylic acid ester. In other words, the structural unit containing a structure having a cyclic ether structure, a cyclic ester structure, or a cyclic carbonate structure in a side chain is preferably a structural unit containing a structure derived from a (meth)acrylic acid ester having a cyclic ether structure, a cyclic ester structure, or a cyclic carbonate structure.
[0066] The polymer may have a structural unit including a structure derived from acrylonitrile, methyl (meth)acrylate, vinyl acetate, vinylpyrrolidone, vinylidene fluoride, etc. The polymer may have a structural unit including a structure derived from a monomer having a plurality of polymerizable groups.
[0067] In one embodiment of the present invention, the polymer is preferably a polymer of a monomer containing an unsaturated cyclic carbonate structure, and more preferably a copolymer of a monomer containing an unsaturated cyclic carbonate structure and a (meth)acrylic acid ester having a cyclic ether structure, a cyclic ester structure, or a cyclic carbonate structure. The polymer may be a copolymer of a monomer containing an unsaturated cyclic carbonate structure and a (meth)acrylic acid ester having a cyclic ether structure. The content of the structural unit containing a structure derived from an unsaturated cyclic carbonate relative to the total structural units of the polymer is preferably 50 mol% or more and 100 mol% or less, more preferably 60 mol% or more and 99 mol% or less, even more preferably 70 mol% or more and 95 mol% or less, and even more preferably 75 mol% or more and 90 mol% or less. The content of structural units including a structure derived from a (meth)acrylic acid ester having a cyclic ether structure, a cyclic ester structure, or a cyclic carbonate structure relative to all structural units of the polymer is preferably 1 mol% to 40 mol%, more preferably 5 mol% to 30 mol%, and even more preferably 10 mol% to 25 mol%. The total content of structural units including a structure derived from an unsaturated cyclic carbonate and structural units including a structure derived from a (meth)acrylic acid ester having a cyclic ether structure, a cyclic ester structure, or a cyclic carbonate structure relative to all structural units of the polymer may be 90 mol% to 100 mol%, or may be 97 mol% to 100 mol%.
[0068] The polymer may be one or more of different types. The polymer may have a three-dimensional network structure formed by interpenetrating or crosslinking a plurality of molecular chains.
[0069] The polymer can be produced by homopolymerizing or copolymerizing the monomers that form each structural unit. For example, when each monomer is a radically polymerizable monomer having a carbon-carbon unsaturated double bond, a polymer having each structural unit can be obtained by a conventionally known radical polymerization method using each monomer and a radical polymerization initiator. A polymer having a structural unit containing a structure having a carbonate group in the main chain can be obtained by reacting an alkylene oxide with carbon dioxide. A polymer having a structural unit containing a structure having an ether group in the main chain can be obtained by ring-opening polymerization of an alkylene oxide (ethylene oxide, propylene oxide, etc.). When the polymer is obtained by polymerization, the polymerization may be performed in a state where a salt X, other lithium salts, etc. are further mixed in addition to each monomer and a polymerization initiator.
[0070] The content of the polymer in the non-aqueous electrolyte is preferably from 50% by mass to 99% by mass, more preferably from 60% by mass to 95% by mass, and even more preferably from 70% by mass to 90% by mass.
[0071] The salt X is a salt having an oxalato complex anion containing elemental boron. By including the salt X in the non-aqueous electrolyte, the charge transfer resistance of the non-aqueous electrolyte storage element can be reduced, and the occurrence of a short circuit due to repeated charging and discharging can be suppressed.
[0072] The oxalato complex anion containing a boron element is typically a complex anion in which at least one oxalato ligand is coordinated to a boron atom. Examples of the oxalato complex anion containing a boron element include a difluorooxalatoborate anion represented by the following formula (1) and a bisoxalatoborate anion represented by the following formula (2), and the like, with the bisoxalatoborate anion represented by the following formula (2) being preferred.
[0073] [ka]
[0074] [ka]
[0075] The salt X may be a lithium salt, a sodium salt, a potassium salt, a magnesium salt, an onium salt, or the like. The salt X is preferably a lithium salt. Examples of the salt X include lithium difluorooxalatoborate (LiDFOB) and lithium bisoxalatoborate (LiBOB), and LiBOB is preferred. The salt X may be used alone or in combination of two or more.
[0076] The content of salt X in the non-aqueous electrolyte is 0.1% by mass to 5% by mass, preferably 0.2% by mass to 4% by mass, more preferably 0.3% by mass to 3% by mass, and even more preferably 0.5% by mass to 2% by mass. By keeping the content of salt X within the above range, it is possible to reduce the charge transfer resistance and suppress the occurrence of short circuits due to repeated charging and discharging.
[0077] Examples of other lithium salts other than the salt X that may be contained in the non-aqueous electrolyte include inorganic lithium salts such as LiPF6, LiPO2F2 (LiDFP), LiBF4, LiClO4, and LiN(SO2F)2, lithium oxalate salts such as lithium difluorobisoxalatophosphate, and lithium salts having halogenated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, LiPF6 or LiN(SO2CF3)2 is preferred, and LiN(SO2CF3)2 is more preferred. The other lithium salts are also preferably imide salts such as LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, and LiN(SO2CF3)(SO2C4F9).
[0078] The content of the other lithium salt in the non-aqueous electrolyte (the number of moles of the other lithium salt per 1 kg of the polymer and the residual monomer) is preferably 0.1 mol / kg or more and 2.5 mol / kg or less, more preferably 0.3 mol / kg or more and 2.0 mol / kg or less, even more preferably 0.5 mol / kg or more and 1.7 mol / kg or less, and particularly preferably 0.7 mol / kg or more and 1.5 mol / kg or less. By setting the content of the other lithium salt within the above range, the ionic conductivity of the non-aqueous electrolyte can be increased.
[0079] The non-aqueous electrolyte may further contain other components in addition to the polymer, salt X, and other lithium salts. Examples of other components include residual monomers of the polymer, non-aqueous solvents, additives, and the like. As the non-aqueous solvent and additives, various conventionally known non-aqueous solvents and additives used in non-aqueous electrolytes of general non-aqueous electrolyte storage elements can be used. The content of the additive in the non-aqueous electrolyte can be, for example, 0.01% by mass or more and 10% by mass or less, and may be 7% by mass or less, 3% by mass or less, or 1% by mass or less.
[0080] The lower limit of the total content of the polymer, salt X and other lithium salts in the non-aqueous electrolyte is preferably 70% by mass, more preferably 80% by mass, and even more preferably 90% by mass, 95% by mass or 99% by mass. The upper limit of the total content of the polymer, salt X and other lithium salts in the non-aqueous electrolyte may be 100% by mass.
[0081] The lower limit of the content of the solid component in the non-aqueous electrolyte is preferably 70% by mass, more preferably 80% by mass, and further preferably 90% by mass, 95% by mass, or 99% by mass. The upper limit of the content of the solid component in the non-aqueous electrolyte may be 100% by mass. The non-aqueous electrolyte is preferably a solid electrolyte. "Solid electrolyte" refers to a non-aqueous electrolyte that is substantially composed of only solid components. "Solid components" refers to components that are solid at 20°C. Generally, polymers, salt X, and other lithium salts correspond to solid components. The non-aqueous electrolyte "substantially composed of only solid components" refers to a content of the solid components in the non-aqueous electrolyte of 99% by mass or more. When the non-aqueous electrolyte is a solid electrolyte, it is possible to further suppress the precipitation of dendrites on the negative electrode surface and suppress leakage. On the other hand, the non-aqueous electrolyte may be used in a gel form containing a suitable amount of a non-aqueous solvent or the like.
[0082] The nonaqueous electrolyte storage element according to one embodiment of the present invention is preferably operated in an environment of 40° C. or higher, and more preferably in an environment of 45° C. or higher. By operating the nonaqueous electrolyte storage element in an environment of 40° C. or higher, the occurrence of short circuits due to repeated charging and discharging is further suppressed. "The nonaqueous electrolyte storage element is operated" may mean that it is charged or discharged, or may be both. The nonaqueous electrolyte storage element may be operated in an environment of, for example, 100° C. or lower, or may be operated in an environment of 80° C. or lower, or 60° C. or lower. The nonaqueous electrolyte storage element may be operated in an environment in a temperature range that is equal to or higher than any of the lower limits described above and equal to or lower than any of the upper limits described above.
[0083] The nonaqueous electrolyte storage element according to one embodiment of the present invention can be used in various applications of conventional nonaqueous electrolyte storage elements, such as power sources for automobiles such as electric vehicles (EVs), hybrid automobiles (HEVs), and plug-in hybrid automobiles (PHEVs), power sources for electronic devices such as personal computers and communication terminals, and power sources for power storage. The nonaqueous electrolyte storage element is particularly suitable for applications that may be used in environments of 40° C. or higher, such as power sources for automobiles.
[0084] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery.
[0085] Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.
[0086] <Method of using non-aqueous electrolyte storage element> The nonaqueous electrolyte storage element according to one embodiment of the present invention can be used in the same manner as a conventionally known nonaqueous electrolyte storage element. In particular, the nonaqueous electrolyte storage element is preferably used in an environment of 40° C. or higher. That is, a method for using the nonaqueous electrolyte storage element according to one embodiment of the present invention includes operating the nonaqueous electrolyte storage element according to one embodiment of the present invention in an environment of 40° C. or higher. In the method for using, it is preferable to operate the nonaqueous electrolyte storage element in an environment of 45° C. or higher. "Operating the nonaqueous electrolyte storage element" may mean charging, discharging, or both. In the method for using, the nonaqueous electrolyte storage element may be operated in an environment of 100° C. or lower, or may be operated in an environment of 80° C. or lower or 60° C. or lower. In the method for using, the nonaqueous electrolyte storage element may be operated in an environment of a temperature range of any of the above-mentioned lower limits or higher and any of the above-mentioned upper limits or lower.
[0087] <Electricity storage device> The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements assembled together in a power source for an automobile such as an EV, HEV, or PHEV, a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, the technique of the present invention may be applied to at least one of the nonaqueous electrolyte storage elements included in the electricity storage unit.
[0088] 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects the two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects the two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of the one or more nonaqueous electrolyte electricity storage elements 1.
[0089] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The method for producing the nonaqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods. The method for producing the nonaqueous electrolyte storage element includes, for example, preparing an electrode body, preparing a raw material solution of the nonaqueous electrolyte, housing the electrode body and the raw material solution of the nonaqueous electrolyte in a container, and polymerizing the raw material solution of the nonaqueous electrolyte. The preparation of the electrode body includes preparing a positive electrode and a negative electrode, and forming the electrode body by stacking or rolling the positive electrode and the negative electrode with a separator interposed therebetween.
[0090] The raw material solution of the non-aqueous electrolyte contains, for example, a monomer, a polymerization initiator, a salt X, other lithium salts, etc. The monomer may be one or more types that form structural units constituting a polymer that is the main component of the non-aqueous electrolyte. The polymerization reaction of the raw material solution of the non-aqueous electrolyte may be carried out by heating or the like depending on the types of the monomer and the polymerization initiator.
[0091] <Other embodiments> The nonaqueous electrolyte storage element and the method of using the nonaqueous electrolyte storage element of the present invention are not limited to the above-mentioned embodiments, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.
[0092] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (e.g., a lithium secondary battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to various secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors.
[0093] In the above embodiment, the electrode body in which the positive electrode and the negative electrode are stacked with a separator interposed therebetween has been described, but the electrode body may not include a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state in which a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. In addition, the electrode body may not include a separator, and the positive electrode and the negative electrode may be electrically isolated only by the solid non-aqueous electrolyte. The non-aqueous electrolyte storage element of the present invention may be manufactured by adopting a method other than the polymerization reaction of the raw material solution of the non-aqueous electrolyte in a container. EXAMPLES
[0094] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0095] [Example 1] A monomer solution was prepared by mixing 100 parts by mass of a monomer obtained by mixing vinylene carbonate (VC) and tetrahydrofurfuryl acrylate (TFA) in a molar ratio of 5:1 with 0.50 parts by mass of azobisisobutyronitrile (AIBN) as a polymerization initiator. 0.5% by mass of lithium bisoxalatoborate (LiBOB), a salt having an oxalato complex anion containing boron as an additive, and 1.0 mol / kg of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as another lithium salt (supporting salt) were dissolved in the monomer solution to obtain a raw material solution of a non-aqueous electrolyte.
[0096] An electrode body was produced by stacking two electrodes, each of which had metallic lithium arranged on copper foil as a substrate, with a separator made of a microporous polyolefin film interposed between them, so that the metallic lithium faced each other, and the electrode body was placed in a container. Next, the obtained raw material solution of the nonaqueous electrolyte was poured into the container and sealed. Next, the container was heated at 60°C for 12 hours to polymerize the monomers contained in the raw material solution, and a nonaqueous electrolyte storage element of Example 1 having a solid nonaqueous electrolyte (polymer solid electrolyte) was produced.
[0097] [Examples 2 to 5, Comparative Examples 1 to 5] Each of the nonaqueous electrolyte storage elements of Examples 2 to 5 and Comparative Examples 1 to 5 was produced in the same manner as in Example 1, except that the types and contents of the additives were as shown in Table 1. In the table, LiDFOB represents lithium difluorooxalatoborate, LiDFP represents lithium difluorophosphate, and PRS represents 1,3-propene sultone.
[0098] (Measurement of charge transfer resistance) The charge transfer resistance was determined by AC impedance measurement for each of the nonaqueous electrolyte storage elements of Examples 1 to 5 and Comparative Examples 1 to 5. Specifically, the diameter of the semicircle of the Nyquist plot obtained by AC impedance measurement was determined as the charge transfer resistance. The electrochemical measurement system "VMP-300" manufactured by Biologic was used as the device for AC impedance measurement. The measurement conditions were a frequency range of 7.0 MHz to 0.10 Hz, an amplitude voltage of 10 mV, and an environmental temperature of 25°C. The measurement results are shown in Table 1.
[0099] (Charge-discharge cycle test) For each of the nonaqueous electrolyte storage elements of Examples 1 to 5 and Comparative Examples 1 to 5, a current density of 0.5 mA / cm was applied in an environment of 25° C. 2 and a capacity density of 1mAh / cm 2 A charge-discharge test was performed under the condition that the current direction was alternately reversed after the current was applied for 100 s. A rest period of 5 minutes was provided after each current application. The charge-discharge cycle was repeated until a short circuit occurred, and the number of cycles until the short circuit occurred was calculated. The occurrence of a short circuit was judged based on whether the overvoltage, which usually increases with repeated charging and discharging, started to decrease. Specifically, when the overvoltage, which increases with repeated charging and discharging, started to decrease compared to the previous cycle, and the overvoltage did not increase again in the subsequent repeated charging and discharging, the point at which the overvoltage started to decrease was judged to be the occurrence of a short circuit. The number of cycles until the overvoltage caused by the above short circuit decreased was defined as the "number of cycles until a short circuit occurred." The measurement results are shown in Table 1.
[0100] [Table 1]
[0101] As shown in Table 1, each of the nonaqueous electrolyte storage elements of Examples 1 to 5, in which a salt having an oxalato complex anion containing elemental boron (LiBOB or LiDFOB) was contained in the nonaqueous electrolyte, had a low charge transfer resistance of 35 Ω or less, and the number of cycles until a short circuit occurred exceeded 40, suppressing the occurrence of a short circuit due to repeated charging and discharging.
[0102] [Examples 6 and 7, Reference Example 1, Comparative Example 6] Each of the nonaqueous electrolyte storage elements of Examples 6 and 7, Reference Example 1 and Comparative Example 6 was produced in the same manner as in Example 1, except that the types and contents of additives were as shown in Table 2.
[0103] (Charge-discharge cycle test) For each of the nonaqueous electrolyte storage elements of Examples 6 and 7, Reference Example 1, and Comparative Example 6, a current density of 0.5 mA / cm was measured under the temperature environment shown in Table 2. 2 and a capacity density of 2.5mAh / cm 2 A charge-discharge test was performed under the condition that the current direction was alternately reversed after the current was applied up to 1000 V. A rest period of 5 minutes was provided after each current application. The charge-discharge cycle was repeated until a short circuit occurred, and the number of cycles until the voltage during current application exceeded 0.2 V and the number of cycles until a short circuit occurred were obtained. The occurrence of a short circuit was judged based on whether the overvoltage, which usually increases with repeated charging and discharging, started to decrease. Specifically, when the overvoltage, which increases with repeated charging and discharging, started to decrease compared to the previous cycle, and the overvoltage did not increase again in the subsequent repeated charging and discharging, the point at which the overvoltage started to decrease was judged to be the occurrence of a short circuit. The number of cycles until the reduction in the overvoltage caused by the above short circuit occurred was defined as the "number of cycles until a short circuit occurred." The measurement results are shown in Table 2.
[0104] [Table 2]
[0105] As shown in Table 2, the nonaqueous electrolyte storage element of Example 6, which contains a salt having an oxalato complex anion containing elemental boron in the nonaqueous electrolyte and is operated in an environment of 40°C or higher, sufficiently suppresses the increase in overvoltage associated with charge / discharge cycles, and significantly increases the number of cycles until short circuit occurs. Here, a comparison between Comparative Example 6 and Reference Example 1 shows that the increase in the number of cycles until short circuit occurs due to the increase in operating temperature is 3.18 times (=35 times / 11 times). Also, a comparison between Comparative Example 6 and Example 7 shows that the increase in the number of cycles until short circuit occurs due to the addition of a salt having an oxalato complex anion containing elemental boron in the nonaqueous electrolyte is 2.09 times (=23 times / 11 times). Comparing Comparative Example 6 with Example 6, it can be confirmed that the increase in the number of cycles until a short circuit occurred due to the inclusion of a salt having an oxalato complex anion containing elemental boron in the non-aqueous electrolyte and increasing the operating temperature was 7.36 times (=81 times / 11 times), which is a higher synergistic effect than the product of the respective effects, that is, 6.65 times (=3.18 times x 2.09 times).
[0106] [Reference example 2] Positive electrode active material Li 1+α (Ni 0.33 Mn 0.67 ) 1-α A positive electrode mixture paste was prepared using a lithium transition metal composite oxide represented by O2 ((1+α) / (1-α)=1.33), acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. The mass ratio of the positive electrode active material, AB, and PVDF was 92.25:4.50:3.25 (solid content conversion). The positive electrode mixture paste was applied to the surface of aluminum foil as a positive electrode substrate and dried. Then, roll pressing was performed to obtain a positive electrode. Metallic lithium was placed on copper foil as a negative electrode substrate to obtain a negative electrode. A non-aqueous solvent consisting of a mixture of fluoroethylene carbonate (FEC) and trifluoroethyl methyl carbonate (TFEMC) in a volume ratio of 30:70 was added with lithium hexafluorophosphate (LiPF6) at a concentration of 1.0 mol / dm 3A non-aqueous electrolyte (nonaqueous electrolyte solution) was obtained by dissolving the non-aqueous electrolyte in a content of 1:1. An electrode assembly was prepared using the positive electrode, the negative electrode, and a separator made of a microporous polyolefin film, and the electrode assembly was placed in a container. Next, a nonaqueous electrolyte was poured into the container and the container was sealed to obtain a nonaqueous electrolyte storage element of Reference Example 2.
[0107] [Reference Examples 3 to 5] Each of the nonaqueous electrolyte storage elements of Reference Examples 3 to 5 was produced in the same manner as Reference Example 2, except that the nonaqueous electrolyte (nonaqueous electrolytic solution) contained additives of the types and amounts shown in Table 3.
[0108] (Initial charge / discharge) The obtained nonaqueous electrolyte storage elements of Reference Examples 2 to 5 were initially charged and discharged under the following conditions in an environment of 25°C. The charging was performed at a constant current and constant voltage with a charging current of 0.1C and a charging voltage of 4.7V, and the charging termination condition was that the charging current was until the charging current reached 0.05C. Then, a rest period of 10 minutes was provided. The discharging was performed at a constant current with a discharging current of 0.1C and a discharging termination voltage of 2.0V. Then, a rest period of 10 minutes was provided. This charging and discharging was performed for two cycles.
[0109] (Measurement of charge transfer resistance) Next, the charge transfer resistance was determined by AC impedance measurement for each of the nonaqueous electrolyte storage elements of Reference Examples 2, 4, and 5. Specifically, the diameter of the semicircle of the Nyquist plot obtained by AC impedance measurement was determined as the charge transfer resistance. The device used for AC impedance measurement was an electrochemical measurement system "VMP-300" manufactured by Biologic. The measurement conditions were a frequency range of 7.0 MHz to 0.10 Hz, an amplitude voltage of 10 mV, and an environmental temperature of 25°C. The measurement results are shown in Table 3. The charge transfer resistance was not measured for the nonaqueous electrolyte storage element of Reference Example 3.
[0110] (Charge-discharge cycle test) Next, the nonaqueous electrolyte storage elements of Reference Examples 2 to 5 were subjected to a charge-discharge cycle test under the following conditions in an environment of 25°C. The charge was a constant current constant voltage charge with a charge current of 0.2C and a charge voltage of 4.7V, and the charge termination condition was until the charge current reached 0.05C. The discharge was a constant current discharge with a discharge current of 0.1C and a discharge termination voltage of 2.0V. A rest period of 10 minutes was provided after each charge and discharge. The charge-discharge cycle was repeated until a short circuit occurred, and the number of cycles until the short circuit occurred was determined. The occurrence of a short circuit was confirmed by the presence or absence of a decrease in the Coulomb efficiency due to an increase in the amount of charged electricity during the charge-discharge cycle. Specifically, it was determined that a short circuit occurred when the amount of charged electricity increased compared to the amount of charged electricity in the immediately preceding cycle and the Coulomb efficiency fell below 97%. The above-mentioned "Coulomb efficiency" is the percentage of the discharge capacity relative to the amount of charged electricity in that cycle. The measurement results are shown in Table 3.
[0111] [Table 3]
[0112] As shown in Table 3, in the nonaqueous electrolyte storage element using a nonaqueous electrolyte, the number of cycles until short circuit occurrence was greater in Reference Example 4 using the same amount of PRS as the additive than in Reference Example 3 using LiDFOB as the additive. This is the opposite result to the result shown in Table 1 that in the nonaqueous electrolyte storage element using a solid electrolyte containing a polymer as the main component, the number of cycles until short circuit occurrence was greater in Example 5 using LiDFOB as the additive than in Comparative Example 4 using the same amount of PRS. In the case of a nonaqueous electrolyte storage element using a nonaqueous electrolyte, the charge transfer resistance is low, whereas in the case of a nonaqueous electrolyte storage element using a nonaqueous electrolyte containing a polymer as the main component, the charge transfer resistance is high, and in the case of a nonaqueous electrolyte storage element using a nonaqueous electrolyte containing a polymer as the main component, it is considered that the increase in resistance due to the inclusion of an additive in the nonaqueous electrolyte greatly affects the short circuit suppression effect. For this reason, it is believed that the types of additives that have a high short-circuit suppression effect are different between nonaqueous electrolyte storage elements that use a nonaqueous electrolyte solution and nonaqueous electrolyte storage elements that use a nonaqueous electrolyte containing a polymer as the main component. [Industrial Applicability]
[0113] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]
[0114] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device
Claims
1. a negative electrode having metallic lithium at least in a charged state; A non-aqueous electrolyte containing a polymer as a main component. Equipped with the non-aqueous electrolyte further contains a salt having an oxalato complex anion containing elemental boron; the content of the salt in the nonaqueous electrolyte is 0.1% by mass or more and 5% by mass or less;
2. 2. The non-aqueous electrolyte storage element according to claim 1, wherein the salt is lithium bis(oxalato)borate.
3. 3. The nonaqueous electrolyte storage element according to claim 1, wherein the content of the salt in the nonaqueous electrolyte is from 0.5% by mass to 2% by mass.
4. The nonaqueous electrolyte storage element according to claim 1 or 2, which is operated in an environment of 40° C. or higher.
5. A method for using a nonaqueous electrolyte storage element, comprising operating the nonaqueous electrolyte storage element according to claim 1 or 2 in an environment at 40° C. or higher.
Citation Information
Patent Citations
Polymer electrolyte material
JP2014185195A
Lithium secondary battery
JP2016100065A